P177 EFFECTS OF PRE-OPERATIVE USE OF BIOLOGIC AGENTS ON INTRA-OPERATIVE BLOOD LOSS, OPERATIVE TIME AND LENGTH OF SMALL BOWEL RESECTION IN CROHN'S DISEASE PATIENTS. (18th January 2018) - Ayoub, Fares; Kamel, Amir; Chaudhry, Naueen; Tan, Sanda; Iqbal, Atif; Zimmermann, Ellen; Glover, Sarah
Abstract: Introduction/Background/Aims: While the effects of biologic agents on post-operative outcomes in Crohn's disease patients is well-established, the effects on intra-operative variables including blood loss, operative time and length of small bowel resection remains to be determined. Methods: We performed a retrospective chart review of patients with Crohn's disease undergoing intestinal resection at the University of Florida Shands Hospital between May 2011 and May 2017. Baseline characteristics, details of pre-operative medication, intra-operative variables (blood loss, total operative time and length of small bowel resection) were collected. Results: Overall, 149 patients underwent intestinal resection during the study time frame. Mean age was 40.9 years, 54.9% were females, mean BMI was 25. Overall, 57 patients were on steroids in the 2 weeks prior to surgery, 104 were on active biologic therapy in the 2 weeks prior to surgery. 74 were on anti-TNFs, 13 on vedolizumab, 6 on ustekinumab, 7 on natalizumab and 4 on tofacitinib. Vedolizumab was associated with lower total operative time (125 minutes vs 170 minutes) (p=<0.001). Tofacitinib use was associated with decreased blood loss (37mL vs 155mL) (p=<0.001) as well as decreased length of small bowel resection (2cm vs 19cm) (p=<0.001). No other significant associations were found with other biologics. In a forward step-wise multi-variable regression, vedolizumab and tofacitinib remained significantly associated with lower total operative time, less length of small bowel resection respectively (p=0.023, p=<0.001). Conclusions: The use of biologics pre-operatively had no negative effects on intraoperative blood loss, length of operative time or amount of small bowel resection. Associations between vedolizumab and shorter operative time as well as tofacitinib and less amounts of blood loss/length of small bowel resection are promising, but require validation in larger patient cohorts.